Cloud Hopping: One Library's Experience Migrating from One LSP to Another. Issue 4 (2nd October 2021) - Nicholson, Joseph; Tokoro, Shoko
ABSTRACT: In 2018 Atkins Library at UNC Charlotte became one of the first libraries to complete a migration to Ex Libris' Alma from OCLC's WorldShare Management Services. Focusing on bibliographic and holdings data, this article describes the challenges that Atkins staff confronted in moving to the new system. They include efforts to remediate data before the migration, problematic initial data loads, communication issues with Ex Libris' migration staff, and unsuccessfully migrated serials holdings data. The article will also focus on data clean-up efforts post-migration and offer a summary of the benefits and drawbacks of the migration.